Analisis Bauran Pemasaran 7P pada Bank BUMN dan Bank Swasta dalam Konteks Green Marketing - Makitsuna, Farhand; Permadi, Didi; Faidah, Delima Syuwi; Izzan, Danial; Muttaqin, Muhammad Zayni (Jurnal Ilmiah Akuntansi Keuangan dan Bisnis (JIKABI), 2024)
The study aims to determine the impact of the 7P marketing mix on BUMN and private banks in terms of sustainability marketing. The 7P Blend is a marketing blend idea that considers things beyond the product. It is expected that green marketing can enhance environmental concern in all aspects of business. The study involved 101 service users from both banks, selected through Google Forms, and processed using SEM-PLS instruments. The results show that location and price influence long-term marketing. These results may indicate that banking services should take into account customer needs for close service locations, affordable prices, and consistent service. It is expected that this will increase customer satisfaction and their loyalty to banking services, so customers will use the services to meet their needs in the long term.